Intervenção ergonômica e o uso da simulação computacional na concepção de produtos: o design de uma plantadora mecanizada de mandioca - Ferrari, Daniel Augusto [UNESP] (2014)
In part of companies in the agricultural industry, it is observed that machinery and equipment projects are developed with ergonomic problems. It is due to lack of knowledge of the subject by the designers involved and the increased costs to adjust the designed systems, and it is also due to consumers who do not require or do not have knowledge of the subject. Through a case study, the author applied the method of ergonomic intervention in the redesign conception of a mechanized cassava planter, respecting the proposed steps: assessment, diagnosis, designing and pre-validation; culminating in a new conceptual proposal. Using graphics computing resources, it was made an analysis of the current project and redesign with ergonomic focus, thorugh analysis simulations of the wrap range of the machines and postural assessment though the use of Digital Human Models (DHM). The results obtained in this research showed that the use of computer simulation to predict ergonomic issues in the conception of agricultural machinery, can be one of the solutions to the beginning of the establishment of ergonomic culture in those sectors